(untitled) - Eliot Hurst, Michael E. (North Scituate, Mass., 1972)
This book introduce toward a geography of economic behavior, some basic concepts, the systems approach. Natural and human milieux. Some models of the natural and human milieux, agricultural systems...
Keywords: Địa lý kinh tế,Economic geography